Geometrical Model of Visible Angle Discrimination - Yu A Chudina (Peoples' Friendship University of Russia (RUDN University), 2012)
The geometrical model of discrimination of four-line diagrammatic representations, made with the multidimensional scaling method of subjective estimations of perceived pairwise differences between pictures is described in the article. The derived geometrical model of the representations, interpreted in terms of Sokolov and Izmailov's spherical model of differentiating stimuli, is presented as a spherical surface in four-dimensional Euclidean space and is characterized by three spherical coordinates. The discrimination of four-line figures is defined by picture configuration characteristics.